Establishing an appropriate overfire air angle at the furnace throat of a low-NOx W-shaped flame furnace. (25th July 2022) - Wang, Xiu; Kuang, Min; Cheng, Shuting; Qi, Shengchen; Huang, Jun; Lin, Weijian
Graphical abstract: Highlights: Deeply low-NO x combustion worsening burnout greatly in W-shaped flame furnaces. Developing a low-NO x and high-burnout solution for this problem. First introducing overfire air at the furnace throat in the solution. Evaluating the overfire air angle's impact on the performance of this solution. Determining an appropriate overfire air angle for the low-NOx solution. Abstract: A cascade-arch-firing low-NO x and high-burnout configuration (CLHC) was developed as a solution for a 600 MWe W-shaped flame furnace suffering from poor burnout under ultra-low NO x combustion conditions. Under the comprehensive low-NO x combustion conditions regulated by the CLHC, overfire air (OFA) was first positioned at the furnace throat in a uniformly flattening OFA port form along the furnace breadth direction. In order to disclose the OFA angle's effect on the furnace performance and meanwhile establish an appropriate angle for the OFA with the above original designs, the in-furnace flow field, coal combustion, and NO x emissions were evaluated at various OFA angles of θ  = 10°, 20°, 25°, 30°, and 35°. Increasing θ only changed a little the symmetry of flow field and combustion morphology, i.e., the symmetry generally deteriorating first and then improving. The OFA penetration in the furnace throat zone initially increased but then worsen as θ increased. In the upper furnace strongly affected by OFA, gas temperatures, high-temperature zone area, and levels of O2 and CO all descended first and then increased with θ, while NO generally undergone an increase-to-decrease trend. Trends of furnace outlet's performance indexes with θ showed that the residual O2 and CO emission generally decreased first and then increased, NO x emissions initially increased but then decreased, while carbon in fly ash undergone an increase-to-decrease trend prior to an increase at θ  = 35°. In view of the above findings and the gained optimal low-NO x and high-burnout performance (NO x emissions of 667 mg/m 3 at 6% O2 and carbon in fly ash of 5.31%), θ  = 30° was taken as an appropriate OFA angle for the CLHC furnace. Compared with a currently advanced low-NO x combustion art, the CLHC reduced further NO x emissions by 26.3% while remained a high burnout achievement.